mRNA Vaccines in the COVID-19 Pandemic: Production, Antibody Formation Mechanism and Advantages of mRNA Vaccines - Marsya Naranissa Puteri Santoso; Hasna Labib Lathiefah; Fadly Hidayaturochman (Yayasan Cendekia Gagayunan Indonesia, 2025)
Vaccines are antigens that are inactivated or attenuated to produce biological products that can stimulate the immune system. The mRNA vaccine is a new type of vaccine in an effort to deal with the coronavirus disease outbreak. An mRNA vaccine is a vaccine that carries the genetic information of a pathogen that is copied in mRNA This literature review uses an online-based literature study, the library sources selected for use are based on relevance to the topic. The stages of vaccine production include sequence cloning, purification, addition of cap structures, in the delivery of mRNA vaccines formulated in the form of lipid nanoparticles. mRNA vaccines are injected intramuscularly which will then trigger immune cells so that adaptive immune cells are formed. mRNA vaccines can be designed to synthesize quickly, mRNA vaccines do not interfere with cellular function or integrate into the host genome.